Animating senses : exploring multi-sensorial art engagement, intercorporeality and wellbeing of elderly people in dementia day care centre - Chun, Rachel Wan Ying (Nanyang Technological University, 2022)
The demographic shift towards a rapidly ageing population in Singapore has seen an increasing prevalence of dementia. As the irrevocable neurodegenerative condition progresses, the individuals and their family inevitably have to rely on community resources and aged care services to meet the increased care needs. While there have been a proliferation of community and centre-based care services to support ageing-in-place policy, efforts looking into creating meaningful and quality programmes, and understanding its effect on the wellbeing of elderly people have been limited. Considering the above, this study foregrounds arts-health practice to offer inventive care for elderly people at Dementia Day Care Centre (DDC) in Singapore. In this study, I have developed, implemented and explored the processes and effect of a multi-sensorial art engagement programme involving the use of participatory arts and music activities on the wellbeing of Older Persons with Dementia (OPWD). Informed by Merleau-Ponty’s concept of intercorporeality, I approached this notion from the praxis of multi-sensorial art engagement. From this outlook, I investigated how intercorporeality shapes and promotes wellbeing, mediated by the affordances of positive affect, interaction and relations that occur with the engagement of participatory arts and music activities. Using a qualitative approach, this draws on participant observation, semi- structured interviews, digital video, field notes and journals. The empirical materials were analysed using strategies in grounded theory, with the findings validated through triangulation. Recognising the individual and collective attributes, the understandings and developments is derived through a discussion and proposed Multi-sensorial Art Engagement Framework for Older Persons with Dementia (OPWD). With the aim of Animating Senses, I proposed multi-sensorial art engagement as a possible alternative for engaging and better care of elderly people in Dementia Day Care Centre (DDC), as I highlight its potential as a meaningful activity option which taps on their current functional abilities.